Prognostic significance of microsatellite instability determined by immunohistochemical staining of MSH2 and MLH1 in sporadic T3N0M0 colon cancer. (11th February 2004) - Parc, Y; Gueroult, S; Mourra, N; Serfaty, L; Fléjou, J-F; Tiret, E; Parc, R
Abstract : Background: Microsatellite instability (MSI) has been identified as a factor with good prognosis and chemosensitivity in stage III C colon cancer. The purpose of this study was to evaluate the routine use of immunohistochemical analysis (immunohistochemical staining of MSH2 and MLH1) to identify T3N0M0 (stage II) colon cancer with MSI and assess the prognostic value of this analysis. The study was conducted in a large cohort of patients in a single institution who had a curatively resected T3N0M0 colon cancer and were not receiving adjuvant therapy. Methods: Between June 1995 and December 2001, 142 patients (77 females) with a mean age of 68 years, suffering from T3N0M0 colon cancer curatively resected and not receiving adjuvant therapy, were checked in terms of their follow up status. The results of colonoscopy, hepatic ultrasonography, chest x ray, and blood carcinoembryological antigen were noted. All tumours were immunohistochemically stained for MSH2 and MLH1. Perineural invasion, lymphovascular invasion, and the presence of vascular neoplastic emboli were assessed. Results: Twenty four patients (17%) had MSI tumours. Patients with MSI and microsatellite stable (MSS) tumours did not differ in terms of age, perineural or lymphovascular invasion, or the presence of vascular neoplastic emboli. Patients with MSI tumours were more frequently female (18/24 v 60/118; p = 0.001) and more frequently suffered from right sided cancer (19/24 v 58/118; p<0.001). Patients with MSI tumours exhibited significantly better recurrence free survival than those with MSS tumours (p = 0.02). Cox analysis identified age and MSI determined by immunohistochemistry as independent predictive factors of good prognosis (p = 0.009, odds ratio 1.04 (1.01–1.08); p = 0.04, odds ratio 7.9 (1.05–59.6)). Conclusions: MSI determined by immunohistochemistry is an independent predictive factor of good prognosis in T3N0M0 colon cancer. The prognosis for MSI T3N0M0 colon cancer is excellent and chemotherapy should not be proposed in these patients as immunohistochemical analysis produces rapid results.